Determinants and prognostic implication of diagnostic delay in patients with a first episode of pulmonary embolism. Issue 171 (November 2018) - Goyard, Céline; Côté, Benoit; Looten, Vincent; Roche, Anne; Pastré, Jean; Marey, Jonathan; Planquette, Benjamin; Meyer, Guy; Sanchez, Olivier
Abstract: Signs and symptoms of pulmonary embolism (PE) are not specific and this can lead to a diagnostic delay. Little is known about the determinants of this delay and its prognostic implication. We conducted a retrospective analysis of a prospective cohort involving 514 patients with a first episode of PE. The diagnostic delay was defined as a time from first symptom onset to diagnosis of >3 days, corresponding of the median time in the population. Multivariable logistic regression analysis was performed to identify determinants of diagnostic delay. Prognostic implication was measured as the occurrence of 30-day all-cause mortality, haemodynamic collapse or recurrent PE. A total of 240 (47%) among 514 patients had a time from first symptom to diagnosis > 3 days. Previous deep vein thrombosis (OR 0.55, 95% Confidence Interval (CI), 0.32–0.93), immobilization (OR 0.52, 95% CI, 0.28–0.96), surgery (OR 0.31, 95% CI, 0.16–0.62), chest pain (OR 0.58, 95% CI, 0.39–0.86), syncope (OR 0.48, 95% CI, 0.23–1.01), dyspnea (OR 2.48, 95% CI, 1.57–3.91) and hemoptysis (OR 3.57, 95% CI, 1.40–9.07) were associated with diagnostic delay. Twenty-two patients (4.3%, 95%CI, 2.8–6.5) experienced an outcome event within 30 days. Among them, 15 patients (6.2% 95%CI, 3.7–10.3) had a diagnostic delay and 7 (2.6%, 95% CI 1.1–5.4) did not (p = 0.039). In this cohort, diagnostic delay is associated with the absence of major risk factors for PE or clinical features such as chest pain or syncope and the presence of dyspnea or hemoptysis. Diagnostic delay is associated with a worse 30-day prognosis. Highlights: Diagnostic delay in patient with pulmonary embolism (PE) is frequent. PE diagnostic delay is associated with the absence of major risk factors for VTE. PE diagnostic delay is associated with the absence of chest pain or syncope. PE diagnostic delay is associated with the presence of dyspnea or hemoptysis. PE diagnostic delay is associated with a worse 30-day prognosis.